2010
DOI: 10.2528/pierb10051305
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Shielding Effectiveness of Single, Double and Laminated Shields for Oblique Incidence of Em Waves

Abstract: Abstract-Shielding prevents coupling of undesired radiated electromagnetic energy into equipment otherwise susceptible to it. In view of this, some studies on shielding effectiveness of different shields against angle of incidence with conductors and conductive polymers using plane-wave theory are carried out in this paper. The plane wave shielding effectiveness of new combination of these materials is evaluated as a function of angle of incidence for Single, Double and Laminated Shields. Conductivity of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 8 publications
1
26
0
Order By: Relevance
“…Observing above results from Figures 4-6, it is noted that the computation value almost coincides with the experimental value in the linear increasing region. It is concluded that the SE of BESF can be calculated by Equation (6). We further change the experimental frequency from 1 GHz to 3.5 GHz, the results is consistent with that of Figures 4-6. …”
Section: Results Verificationsupporting
confidence: 79%
See 2 more Smart Citations
“…Observing above results from Figures 4-6, it is noted that the computation value almost coincides with the experimental value in the linear increasing region. It is concluded that the SE of BESF can be calculated by Equation (6). We further change the experimental frequency from 1 GHz to 3.5 GHz, the results is consistent with that of Figures 4-6. …”
Section: Results Verificationsupporting
confidence: 79%
“…Assuming the number of samples is N , the SE S i of the ith sample is calculated by Equation (6). The SE Se i of the ith sample is obtained from experiments.…”
Section: Computation Accuracymentioning
confidence: 99%
See 1 more Smart Citation
“…In this way, polymer-based carbon-filled composites [14], or a sandwich of conductive polymer between a conductor and microwave absorber (i.e., Ca-NiTi hexa ferrite, carbonyl-iron particles, barium ferrites, MnZn ferrite) [15] can be used for wideband microwave shielding structures. Other laminated shields are considered as the combination of several layers constructed using conductive polymer, i.e., polyacetylene and poly-p-phenylenebenzobis-thiazole (PBT), doped with iodine, and conducting materials like copper and aluminum [16]. The protection of a sensitive carsize system against electromagnetic waves have been proposed using a shielding cover composed of a 4 layer stuff, aluminum, polyethylene, aluminum and polyester [17].…”
Section: Introductionmentioning
confidence: 99%
“…We have described the framework of the SE computation of the garment. In addition, a number of studies focus on the EMS fabric and textile products, such as model construction of blended EMS fabric [8,9], performance analyses of blended EMS fabric [10,11], computation of blended EMS fabric [12,13], and influence factors analyses of blended EMS fabric [14,15]. Sufficient information about the SE of products in other fields can be found in literature [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%